Graphene-MoS2 with TiO2SiO2 layers based surface plasmon resonance biosensor: Numerical development for formalin detection - Md Biplob Hossain; Md Masud Rana; Lway Faisal Abdulrazak; Saikat Mitra; Mostafizur Rahman (Biochemistry and Biophysics Reports, 2019)
In this article, numerically a surface plasmon resonance (SPR) biosensor is developed based on Graphene-MOS2 with TiO2SiO2 hybrid structure for the detection of formalin. Based on attenuated total reflection (ATR) method, we used angular interrogation technique to sense the presence the formalin by observing the change of “minimum reflectance with respect to SPR angle” and “maximum transmittance with respect to surface plasmon resonance frequency (SPRF)”. Here, we used Chitosan as probe analyte to perform chemical reaction with formalin (formaldehyde) which is consider as target analyte. Simulation results show a negligible variation of SPRF and SPR angle for improper sensing of formalin that confirms absence of formalin whereas for proper sensing is considerably countable that confirms the presence of formalin. Thereafter, a comparison of sensitivity for different sensor structure is made. It is observed that the sensitivity without TiO2, SiO2, MoS2 and Graphene (conventional structure) is very poor and 73.67% whereas the sensitivity with graphene but without TiO2, SiO2 and MoS2 layers is 74.67% consistently better than the conventional structure. This is due to the electron loss of graphene, which is accompanying with the imaginary dielectric constant. Furthermore, the sensitivity without TiO2, SiO2 and graphene but with MoS2 layer is 79.167%. After more if both graphene and MoS2 are used and TiO2 and SiO2 layers are not used then sensitivity improves to 80.5%. This greater than before performance is due to the absorption ability and optical characteristics of graphene biomolecules and high fluorescence quenching ability of MoS2. Further again, if TiO2SiO2 composite layer is used with the Graphene-MoS2 then the sensitivity enhances from 80.5% to 82.5%. Finally, the sensitivity for the proposed structure has been carried out, and result is 82.83%, the highest value among all the previous structures to integrate the advantages of graphene, MoS2, TiO2 and SiO2. Keywords: ATR, Biosensor, Surface plasmon resonance, Formalin, Resonance angle, Resonance frequency, Graphene, MoS2, TiO2, SiO2